Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.47119/ijrp100781620211977
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different solvent extracts from the aerial parts of Costus speciosus (Koen.) for the potential antibacterial activity against selected human pathogenic bacteria

Abstract: Costus speciosus (Koen ex.Retz.) is an ornamental plant and has also been used in traditional medicinal systems, mainly in India and Sri Lanka. This research article reveals the antibacterial activity of the leaves of Costus speciosus (Koen.) and its efficacy in different solvents, acetone, ethanol and sterilized distilled water (aqueous), against selected human pathogenic bacteria, Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). The leaves were tested for antibacterial activity, using agar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…GC-MS phytochemical analysis of these extracts confirmed that most of the active compounds were lipophilic fatty acids 37 . However, another study reported that C. speciosus leaf hexane, methanol and aqueous extracts showed no activity against B. subtilis, E. coli, K. pneumoniae, and S. aureus 17 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GC-MS phytochemical analysis of these extracts confirmed that most of the active compounds were lipophilic fatty acids 37 . However, another study reported that C. speciosus leaf hexane, methanol and aqueous extracts showed no activity against B. subtilis, E. coli, K. pneumoniae, and S. aureus 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies on the antibacterial activity of C. speciosus focused on rhizome extracts. One such study found that the aqueous extract of the plant rhizome was effective against S. aureus, Staphylococcus epidermis, E. coli, P. aeruginosa, and S. typhimurium 38 17 . However, the aqueous extract of plant rhizome showed no such activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation